Student Responses to the Application of the Storytelling Method in Arabic Speaking Skills for High School Students - Yetty Aisya Rosmitha; Farikh Marzuki Ammar (Universitas Muhammadiyah Sidoarjo, 2022)
Learning at SMA Muhammadiyah 1 Taman uses the syllabus set by the Ministry of Religion of the Republic of Indonesia, which is called K-13. Which in the implementation of Arabic language learning at SMA 1 Muhammadiyah Taman uses the storytelling method. The application of the story telling method is carried out in 3 stages, namely opening, core activities, and closing. Student responses to the application of this storytelling method are very good. blackboard projection. In practice, learning at SMA Muhammadiyah 1 Taman is carried out offline and online using zoom during a pandemic. the use of the Storetelling method in teaching speaking skills is an effective indication. Based on the questionnaire processing of student responses to the application of the storytelling method, a score of 83.2% was obtained which was included in the very strong category, namely between 81%-100%. So from the results of this questionnaire, it can be seen that the storytelling method was responded well by students.